Nasal mucocelia transport of chronic rhinitis patients before and after gurah. - Supomo Sukardono Supomo Sukardono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Bacground: " Gurah" is a traditional treatment for nasal and lower respiratory tract diseases or for establishing clearer voice, where the extract " Srigunggu" or "Sirgunggu" is used as nasal drop. The side effect of "gurah" on the mucocilliary system has not been known yet.Objective: The study was done to know the effects of "Gurah" on the mucocilliary transport, in chronic rhinitis patients.Method: The study was performed by pretest-posttest design.The study was performed at "Gurah" location of Kyai Hisyam, Giriloyo, Wukirsari, Imogiri, Kabupaten Bantul Daerah Istimewa Yogyakarta. The mucocilliary transport time of the subjects with chronic rhinitis were tested with saccharine method for three times i.e. on the second (Wt2) and the tenth day (Wt10) after "gurah". Procedure of the "gurah" was done by KH Hisyam himself, and the measurement of mucocilliary transport time was done by the author. The paired-t test was used to test the significant difference of the mucocilliary transport time between before and after "gurah".Result: On the second day after "gurah" there was significant difference of the mucocilliary transport time between before "gurah" and after "gurah" (P< 0.05), but on the tenth day after "gurah", there was no significant difference of the mucocilliary transport time (P>0.05).Conclusion: The mucocilliary transport time was prolonged significantly on second day after "gurah", but on the tenth day the mucocilliary transport time returned to the before ''gurah" value.Key word: "Gurah" - mucociliary transport time